Exploring Wage Returns to Korean Language Proficiency Using a Semi-parametric Analysis - Baik, Junghyun (RIO : revista internacional de organizaciones, 2025)
This study investigates the wage returns to Korean as the official language in South Korea's labor market, focusing on its influence on earnings and the potential nonlinearity in this relationship. Using nationally representative survey data from the Korean Education and Employment Panel Survey 1 (KEEP1), Korean proficiency is measured through reverse-coded levels of the College Scholastic Ability Test (CSAT) Korean Subject. Ordinary Least Squares (OLS) regression, spline functions, and semi-parametric kernel regression are applied to capture both linear and nonlinear wage effects. A differencing method is employed to control for confounding variables such as education and work experience, isolating the independent impact of Korean proficiency. The findings reveal that higher Korean proficiency levels are linked to accelerated wage premiums, possibly reflecting the broader importance of advanced linguistic skills in the Korean labor market. In contrast, lower proficiency levels could be associated with wage penalties, possibly due to linguistic difficulties that limit job opportunities and productivity. Notably, the sample comprises young adults aged 25 to 30 (with an average age of 27.56), which suggests that the observed effects may reflect early career dynamics where linguistic skills play a particularly pronounced role. These results underscore the dual role of Korean proficiency as both a component of human capital and a signaling mechanism, influencing hiring decisions and wage determination in the labor market. This study contributes to the literature by providing empirical evidence on the wage effects of official language proficiency, highlighting its nonlinear influence on earnings. The findings suggest that higher Korean proficiency yields increasing wage premiums, emphasizing the role of advanced language skills in professional success. Additionally, the study underscores the importance of aligning language education policies with labor market demands. Expanding beyond basic literacy, targeted educational and training programs should incorporate advanced linguistic competencies to enhance both academic and workplace language proficiencies, ultimately reducing linguistic disparities in economic opportunities.